2011
DOI: 10.1016/s1995-7645(11)60161-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the anti–diabetic properties of Mucuna pruriens seed extract

Abstract: The study clearly supports the traditional use of M. pruriens for the treatment of diabetes and indicates that the plant could be a good source of potent antidiabetic drug.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(32 citation statements)
references
References 13 publications
0
29
0
3
Order By: Relevance
“…However, it was observed in certain dose only, not in all of the dosas gave the effect of significant weight gains. This dosedependent effects could be happen, similar to dose-dependent effects on weight gains when the ethanol extract of Mucuna pruriens seeds administered to diabetic rats [10] and dose and timedependent effects on sexual behavior when the ethanol extract of Mucuna pruriens seeds administered to normal male rats [3].…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…However, it was observed in certain dose only, not in all of the dosas gave the effect of significant weight gains. This dosedependent effects could be happen, similar to dose-dependent effects on weight gains when the ethanol extract of Mucuna pruriens seeds administered to diabetic rats [10] and dose and timedependent effects on sexual behavior when the ethanol extract of Mucuna pruriens seeds administered to normal male rats [3].…”
Section: Discussionmentioning
confidence: 79%
“…In many countries, this plant is also used in the treatment of cholesterol, diabetes, hypertension, paralysis, rheumatism, cancer, tumors, tuberculosis, asthma, cholera, diarrhea, dysentery, irritation, burns, cough, muscle pain, and many others [5][6][7]. Various studies reported the bioactivity of Mucuna pruriens, such as increasing the sexual activity of normal male rats, hepatoprotective activity with increasing the in vivo antioxidants [8], antidiabetic activity [9][10][11][12], and as a potential antiparkinson from the seeds [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Several research studies have been conducted on the antidiabetic activities of the seeds of MP through biochemical and hematological studies. However, most of this research was short term and no histopathological and histomorphometric parameters were incorporated [6] . were measured by using a one -touch glucometer (Accu Chek, Roche Diagnostics, USA) and animals showing value > 150mg/dl of BGL were selected for the drug study [7] .The animals were kept under standard laboratory conditions, fed with standard pellet diet and water ad libitum.…”
Section: Introductionmentioning
confidence: 99%
“…Mucuna pruriens has proven to be more effective than L-DOPA in parkinson's disease in an animal model [26]. It also shows antidiabetic [27], anticancer [28], anti-oxidant [29], anti-hyperlipidemic [30] and protective effect against nephrotoxicity [31]. These reports led us to hypothesise that high content of dopamine in Mucuna pruriens seed could serve as a potent therapeutic agent for the obesity.…”
Section: Introductionmentioning
confidence: 99%